Determinators of clinical outcomes in patients with chronic arthritis and systemic connective tissue disorders: COVID-19 pandemic focus - Pušica, Irena; Pušica, Irena; Lapćević, Mirjana; Ratković, Stojanka; Manić, Marina; Arapović, Mirjana (General Practice, 2024)
Introduction. Early diagnosis and treatment improve clinical outcomes, especially in chronic arthritis (CA) and systemic connective tissue disorders (SCTD). Thanks to clinical research from the 1990s on and innovative drugs, 55 million life-years have been saved. The COVID-19 pandemic brought on medical challenges in rheumathology. Objective. The study objective was to research early diagnosis, time of the introduction of innovative therapy, participation in clinical research, influence of gender, age, and corticosteroid treatment on hospitalization rate due to COVID- 19 infection in CA and SCTD patients. Method. In November 2022 we performed the crosssectional study in CA and/or SCTD patients using an online questionnaire. The first part of the analyzed questions referred to sociodemographic characteristics and data concerning rheumatic disease - rheumatoid arthritis (RA) and other rheumatic diseases. The second part referred to COVID-19. Data were analyzed by descriptive statistics and Pearson’s Chi-square test using SPSS 29. Results. Out of the total of 176 participants, RA was present in 60,8%. The time from the symptom onset to diagnosis was longer than two years. RA was more frequently diagnosed in the first six months (p < 0,05 - males). The innovative therapy was used by 59,7% of the participants. The majority of RA patients got innovative therapy after five years from disease onset, which is later than in other CAs (p < 0,05 - females). There were 23,3% of the participants who took part in clinical research, more those with RA (p < 0,05 - females). Corticosteroid therapy influenced a higher rate of hospitalization during COVID-19 infection (p < 0,05 - females). Conclusion. Males suffering from RA were diagnosed sooner, while females with RA participated more in clinical research but were later introduced to innovative therapy. The use of glucocorticoid therapy in the treatment of CA and SCTD increased the risk of hospitalization due to COVID-19 infection.